POLA KOMUNIKASI PELATIH DAN ATLET DALAM MENINGKATKAN PRESTASI DI UNIT KEGIATAN MAHASISWA TAEKWONDO UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This study presents two items of problem formulation, namely: first, the pattern of communication between coaches and athletes of Taekwondo UKM UIN Alauddin Makassar in improving achievement. Second, what are the inhibiting factors between coaches and athletes of Taekwondo at UKM UIN Alauddin Makassar? This research uses qualitative methods with a communication approach and is discussed descriptively. Primary data was obtained from Taekwondo UKM coaches and athletes UIN Alauddin Makassar. Data collection is used through observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusions. The results of this study show that: first, the applied communication pattern involves all channels or all team members, where coaches can interact with all athletes to respect each other and create training spirit for increased performance. It involves providing direction and motivation both during practice and when facing the championship. Communication patterns also include wheel patterns and circle patterns at the training stage that occur between the coach and the athlete. Second, coaches and athletes have faced various obstacles, including obstacles in the communication process such as difficulties in sending messages, obstacles in encoding symbols, language barriers, and difficulties faced by message recipients. In addition, they also face obstacles in training, obstacles in championships, semantic barriers, and psychological barriers.